Psychological aspects and fertility issues of GTD. (July 2021) - Di Mattei, Valentina; Mazzetti, Martina; Perego, Gaia; Rottoli, Sara; Mangili, Giorgia; Bergamini, Alice; Cioffi, Raffaella; Candiani, Massimo
Abstract: Gestational trophoblastic disease (GTD) represents a spectrum of rare pregnancy-related disorders, including both premalignant and malignant entities. Although GTD's medical outcomes have been widely explored, limited data are available regarding the related psychological, sexual, and fertility issues. The present chapter aims to enhance comprehension of the psychosocial impact of GTD by discussing the main quantitative and qualitative evidence available in this field. Although patients globally report a good quality of life, clinically significant levels of anxiety and depression have been consistently found across studies. Similarly, despite the quality of couple relationships being generally satisfactory, they often complain of a lack of sexual desire. Moreover, pregnancy loss may raise significant and long-term fertility-related concerns. Specific socio-demographic and clinical factors have been identified as predictors of psychosocial outcomes. At the clinical level, research suggests that there is a need to provide multidisciplinary care to patients. Highlights: Gestational trophoblastic disease (GTD) may produce significant psychosocial consequences on both patients and partners. Although women report a good quality of life, significant distress symptoms have been consistently found across studies. Lack of sexual desire and persistent fertility concerns are complained by a substantial proportion of couples. Younger women, affected by high-risk disease, with no children, and poor social support need particular attention. Multidisciplinary care plans should be developed to address all the relevant issues related to GTD.